Sécurité et Développement - Agnès Bergeret (Revue de la Régulation)
This article describes the transformations of the content of the policies presented by the words “security” and “development”, in Guatemala, since the fifties. Indeed, this country is exemplary of the passage from developmentist policies mixed with repressive military strategies presented as security policies, to a democracy, presented as a rupture introducing a citizen security, which has betted on a liberal development. Alas, this type of development leads to real and serious food, economic and social insecurities. Our analysis is rooted in the study of a particular case – a municipality with a native and peasant majority – to show how the words of the public policies are traduced by the local actors in their configuration of the power struggle: Are revealed the links between violence, juridical evolution, monetarization and commoditization of the property of land.